Study on the Cotton Fabrics with Photoinduced Reversibly Switchable Wettability - Caining Zhang; Xuman Wang (Journal of Nanotechnology)
Superhydrophobic cotton fabric with photoinduced reversibly switchable wettability was prepared by a coating of the hydrophobic copolymer and α-Fe2O3 nanoparticles. The surface morphology of the fabric was observed by scanning electron microscope (SEM). The wettability of the surface was tested under UV illumination and after storage in the dark. The chemical composition of the cotton fabric surfaces before and after UV illumination was analyzed using an X-ray photoelectron spectroscope (XPS) and FTIR. The experimental results showed that the prepared cotton fabric exhibited the excellent superhydrophobic property with a contact angle (CA) of 157.3 ± 2.9°, and became superhydrophilic after UV illumination for 64 h. The surface wettability reverted back to its initial superhydrophobic state after being stored in the dark for 30 d. Based on the XPS and FTIR analyses, the possible mechanism was discussed, and the switchable wettability was caused by the content change of the hydroxyl groups on the α-Fe2O3 surface. Moreover, the superhydrophobic cotton fabric also became superhydrophilic after sunlight illumination for 120 h.